2019
DOI: 10.1111/1468-4446.12697
|View full text |Cite
|
Sign up to set email alerts
|

Transnational queer sociological analysis of sexual identity and civic‐political activism in Hong Kong, Taiwan and mainland China

Abstract: The sociology of homosexuality lacks engagement with queer theory and postcolonialism and focuses primarily on the global metropoles, thus failing to provide a plausible account of non‐Western non‐normative sexual identities. This research adopts the author’s newly proposed transnational queer sociology to address these deficiencies. First, it critiques the Western model of sexual identity predominantly employed to elucidate non‐Western, non‐normative sexualities. It does so by examining not only the queer flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…In Western studies, it has also generally been found that, compared with lesbians, gay men engaging in online dating tend to attach less importance to monogamy and hold more open attitudes toward uncommitted sex (Potârcă et al., 2015). Such gender differences, coupled with the emphasis on familial stability in Chinese culture (Kong, 2019), might explain why the majority of participants in my study expressed a strong desire for a monogamous and stable family relationship with their partner. In short, the above‐mentioned gendered, familial, and socio‐political factors play a role in some lalas' decision to turn their backs on cyberspace and devote their energy to their careers.…”
Section: Resultsmentioning
confidence: 96%
“…In Western studies, it has also generally been found that, compared with lesbians, gay men engaging in online dating tend to attach less importance to monogamy and hold more open attitudes toward uncommitted sex (Potârcă et al., 2015). Such gender differences, coupled with the emphasis on familial stability in Chinese culture (Kong, 2019), might explain why the majority of participants in my study expressed a strong desire for a monogamous and stable family relationship with their partner. In short, the above‐mentioned gendered, familial, and socio‐political factors play a role in some lalas' decision to turn their backs on cyberspace and devote their energy to their careers.…”
Section: Resultsmentioning
confidence: 96%
“…I think that's the goal of this 'humanity' tool," she continued. This tactic of showing the general public that a minoritized community is "just as human as they are" has a long history within LGB and queer activism in mainland China and further afield (see, for example, Cheng 2006;Zivi 2014;Richardson 2017;Bao 2018;Kong 2019). By focusing less on their difference and more on how they are "just like" the cisgender and heteronormative society, these primarily gay and lesbian activists have been able to redefine normative behavior to include their expressions of same-sex attraction.…”
Section: Human Rights To Humanitymentioning
confidence: 99%
“…It is perhaps ironic that the foreign law that opponents claimed expats were trying to force the Hong Kong government to followthe ICCPR-was also enshrined in the Hong Kong Basic Law. When I asked why opponents to the GRO would say that human rights law was foreign, one of the local activists replied, "They think that if Hong Kong has to follow the same rules as everyone else, interactions that existed prior to the British do not exactly map onto Western understandings of the LGB community (Chou 2000; see also Blackwood 1995;Jackson 2001;Kong 2011;Boellstorff 2012;Bao 2018 for a nonexhaustive list of different forms of same-sex eroticisms that do not easily map onto the Western LGB model).…”
Section: Human Rights To Humanitymentioning
confidence: 99%
See 1 more Smart Citation
“…This line of thought on making South–South connections has a profound impact on queer studies in the context of Asia. For example, Travis S. K. Kong’s (2019) “transnational queer sociology” focuses on queer cultures in different parts of the Chinese-language societies in order to tease out how globalization and various forms of state governance have combined to shape queer cultures in distinct ways. Howard Chiang, Ari Larissa Heinrich, and Alvin K. Wong (Chiang & Heinrich, 2013; Chiang & Wong, 2020) come up with the critical term “queer Sinophone cultures” to decenter the PRC (People’s Republic of China)-centrism in transnational queer studies.…”
Section: The Global Southmentioning
confidence: 99%